2017
DOI: 10.3390/nu9030182
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Maternal Plasma Leptin and Adiponectin Concentrations and Newborn Adiposity

Abstract: Increased maternal blood concentrations of leptin and decreased adiponectin levels, which are common disturbances in obesity, may be involved in offspring adiposity by programming fetal adipose tissue development. The aim of this study was to assess the relationship between maternal leptin and adiponectin concentrations and newborn adiposity. This was a cross-sectional study involving 210 healthy mother-newborn pairs from a public maternity hospital in São Paulo, Brazil. Maternal blood samples were collected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
1
16
1
3
Order By: Relevance
“…Prior research has not consistently shown a concomitant relationship between maternal leptin levels and AT development in offspring . Consistent with other studies , we observed that lower cord blood leptin was associated with heavier 3‐ and 4‐year‐old children with higher BMI percentiles.…”
Section: Discussionsupporting
confidence: 90%
“…Prior research has not consistently shown a concomitant relationship between maternal leptin levels and AT development in offspring . Consistent with other studies , we observed that lower cord blood leptin was associated with heavier 3‐ and 4‐year‐old children with higher BMI percentiles.…”
Section: Discussionsupporting
confidence: 90%
“…Despite some significant positive associations at 3 and 4 years of age with sum of skinfolds and percent body fat, the investigators concluded that cord blood concentrations of HMW adiponectin did not seem to be a useful biomarker of adiposity in early childhood . It may even be debated whether birth levels are reflective of neonatal adiposity . Our results suggested only positive associations with adiponectin levels among twins.…”
Section: Discussioncontrasting
confidence: 67%
“…Several studies have reported that adipose VLDLR gene expression can be regulated by PPARγ (Takazawa et al, 2009;Tao and Hajri, 2011;Gao et al, 2014). All these results suggested that VLDLR is important in regulating fat accumulation (Clemente-Postigo et al, 2011;Go and Mani, 2012;Rankinen et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Polymorphism-trait association studies cannot determine whether VLDLR is responsible for variation in a trait or whether a closely linked locus influences the trait. Many studies have revealed that obesity candidate genes were associated with genetics, nutritional disease, gastrointestinal and developmental disorders, and cancer (Castro et al, 2017;Ning et al, 2017). Peroxisome proliferator-activated receptor alpha (PPARα) and retinoid X receptor alpha (RXRα) were identified as central nodes, also called hub molecules (Kunej et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation